Prosedur Penagihan Pajak Melalui Surat Teguran dan Surat Paksa Dalam Perspektif Ekonomi Syariah di Kantor Pelayanan Pajak Pratama Ngawi - Kasmiati Kasmiati; Jullio Fandy Krisma (LABATILA : Jurnal Ilmu Ekonomi Islam, 2022)
Tax is a potential state revenue to support national development. There are many ways that the Directorate General of Taxes does to increase state revenues from the tax sector, one of which is by implementing tax collection. Tax collection with letters of reprimand and letters of coercion is an effort by the government to encourage the community to be responsible and play a role in development development. However, tax collection that has been done as much as possible has not made tax arrears decrease. The purpose of this study is to determine the procedure for collecting taxes with letters of reprimand and letters of compulsion, and to find out the obstacles that occur in tax collection. The research approach used is descriptive qualitative using primary data collection techniques through interviews and observations, and secondary data obtained through documentation. The results of this study indicate that most of the tax collection carried out is in accordance with the regulations. However, in the case of submitting letters, they often encounter obstacles, including taxpayers who do not understand their taxation, invalid addresses, and tax underwriters who cannot pay off their debts and then apply for installment payments.